When Proteomics Reveals Unsuspected Roles: The Plastoglobule Example - Bréhélin, Claire; Nacir, Houda (Frontiers in Plant Science, 2013)
Plastoglobules are globular compartments found in plastids. Before initial proteomic studies were published, these particles were often viewed as passive lipid droplets whose unique role was to store lipids coming from the thylakoid turn-over, or to accumulate carotenoids in the chromoplasts. Yet, two proteomic studies, published concomitantly, suggested for the first time that plastoglobules are more than "junk cupboards" for lipids. Indeed, both studies demonstrated that plastoglobules do not only include structural proteins belonging to the plastoglobulin / fibrillin family, but also contain active enzymes. The specific plastoglobule localization of these enzymes has been confirmed by different approaches such as immunogold localization and GFP protein fusions, thus providing evidence that plastoglobules actively participate in diverse pathways of plastid metabolism. These proteomic studies have been the basis for numerous recent works investigating plastoglobule function. However, a lot still needs to be discovered about the molecular composition and the role of plastoglobules. In this chapter, we will describe how the proteomic approaches have launched new perspectives on plastoglobule functions.